Quantitative Inhibition of Haemophilus influenzae by Trimethoprim/Sulfamethoxazole - Pelton, Stephen I. (1977)
We evaluated the inhibitory effect of trimethoprim (TMP) and sulfamethoxazole (SMZ), alone and in combination, against 34 strains of Haemophilus influenzae. Growth inhibition was determined after incubation for 18 h by comparing viable counts of cultures in drug-containing medium with corresponding counts of control cultures in drug-free medium. In a modified, thymidine-deficient Levinthal broth, the numbers of colony-forming units of all the isolates tested were reduced 100-fold or more by TMP/SMZ (1.25/25 μg/ml) as compared with growth without drug. Inhibition was significantly greater with TMP/SMZ than with either TMP or SMZ alone. Ampicillin-susceptible and ampicillin-resistant strains were equally susceptible to TMP/SMZ. Growth of nontypable strains was inhibited more than growth of type b organisms.